Differences in Interleukin-6 Levels, Neutrophil Levels, and Length of Hospitalization in Pneumonia Patients with and without Garlic Supplementation (Allium sativum) - Irawan, Yogie; Harsini, Harsini; Sutanto, Yusup Subagio (Jurnal Respirologi Indonesia, 2024)
bacteria, viruses, fungi, or parasites, with high mortality and morbidity rates. The examination of IL-6 and neutrophils helps in diagnosis as a marker of inflammation, a predictor of mortality and morbidity, and is useful in evaluating the outcome of treatment. Garlic and its organosulfur content possess anti-inflammatory activity that has the potential to be used as additional therapy in pneumonia patients.Methods: A clinical study with a pretest-posttest quasi-experimental design was conducted on pneumonia patients who were hospitalized at Dr. Moewardi General Hospital, Surakarta from August to October 2022 by consecutive sampling. The treatment group (n=20) received standard therapy plus 3.5 mg of garlic capsules per day for 6 days, while the control group (n=20) received standard therapy. Levels of IL-6 and neutrophil were calculated on the first and sixth days, while the length of hospitalization was calculated from when the patient was admitted until discharge.Results: There was a significant IL-6 difference in the treatment group (P=0.027) and a neutrophil difference in the treatment group (P=0.025) compared to the control group, but there was no significant difference (P=0.876) in the length of stay in the treatment group compared to the control group.Conclusion: Giving garlic as a supplemental therapy to pneumonia patients could significantly reduce IL-6 and neutrophil levels.